How to Teach Medical Students About Pain and Dementia: E-Learning, Experiential Learning, or Both?. Issue 10 (8th August 2020) - Moehl, Keelin; Wright, Rollin M; Shega, Joseph; Malec, Monica; Kelley Fitzgerald, G; Robbins-Welty, Gregg; Zoberi, Kimberly; Tait, Raymond; Perera, Subashan; Deverts, Denise; Horvath, Zsuzsa; Weiner, Debra K
Abstract: Objective: Pain management in persons with mild to moderate dementia poses unique challenges because of altered pain modulation and the tendency of some individuals to perseverate. We aimed to test the impact of an e-learning module about pain in communicative people with dementia on third-year medical students who had or had not completed an experiential geriatrics course. Design: Analysis of pre- to postlearning changes and comparison of the same across the student group. Setting: University of Pittsburgh School of Medicine and Saint Louis University School of Medicine. Subjects: One hundred four University of Pittsburgh and 57 Saint Louis University medical students. Methods: University of Pittsburgh students were randomized to view either the pain and dementia module or a control module on pain during a five-day geriatrics course. Saint Louis University students were asked to complete either of the two modules without the context of a geriatrics course. A 10-item multiple choice knowledge test and three-item attitudes and confidence questionnaires were administered before viewing the module and up to seven days later. Results: Knowledge increase was significantly greater among students who viewed the dementia module while participating in the geriatrics course than among students who viewed the module without engaging in the course ( P < 0.001). The modules did not improve attitudes in any group, while student confidence improved in all groups. Conclusions: Medical students exposed to e-learning or experiential learning demonstrated improved confidence in evaluating and managing pain in patients with dementia. Those exposed to both educational methods also significantly improved their knowledge.